Food Crisis or the Deepening of Inequity? The Systemic Crisis of the Global Village - Huaylupo Alcázar, Juan (2009)
The current world crisis is neither alimentary nor financial, it is a crisis of the prevailing system that is trying to reshape itself in the face of its contradictions and inoperance as market rules is concerned. However, the prevailing ideological and cognoscitive horizon leaves little space as to appreciate social welfare as an alternative as a way out of the crisis.